Catalytic transesterification of beta-ketoesters with zeolite H-FER under solvent free conditions - Chavan, Subhash P.; Pasupathy, K.; Shengule, S.; Shinde, V.; Anand, R. (Arkivoc, 2005)
Zeolite H-FER catalyzes the transesterification of beta-ketoesters with variety of alcohols under solvent-less condition in excellent yields. The catalyst can be reused without any loss of activity.
Keywords: ferrierite; transesterification; zeolite

Corrosion protective poly(o-toluldine) coatings on copper - Shinde, V.; Sainkar, S. R.; Patil, P. P. (Corrosion Science, 2005)
This study examines the use of poly(o-toulidine) (POT) coatings for corrosion protection of copper (Cu) in an aqueous solution of 3% NaCl. The POT coatings were synthesized on Cu substrates under cyclic voltammetric conditions from an aqueous solution of sodium oxalate. The resulting, POT coatings were uniform, shiny and strongly adherent to the Cu substrates. These coatings were characterized by cyclic voltammetry (CV), UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The ability of POT to serve as a corrosion protective coating for Cu was examined by potentiodynamic polarization measurements and CV. The results of this study clearly reveal that the POT acts as corrosion protective coating on Cu and reduces the corrosion rate of Cu almost by a factor of 40. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: Conducting polymer coatings; Copper; Corrosion resistant coatings; cyclic voltammetry; poly(o-toluidine) coatings